THE ROLE OF SOCIAL WORKERS IN CASE RESOLUTION BASED IN THE DIGITAL ERA - Rendi Mark Sowaha Duha; Rahmayanti (PT. Radja Intercontinental Publishing, 2026)
The digital era has brought significant changes to various aspects of life, including the legal case resolution system. Amid this transformation, the role of social workers has become increasingly crucial as a bridge between clients and judicial institutions that now operate based on digital technology. This study aims to analyze the role of social workers in the case resolution process in the digital era, including assistance, mediation, and advocacy. The method used is qualitative research with a case study approach through in-depth interviews, observation, and documentation studies. The results show that social workers have a strategic role in facilitating access to justice for vulnerable groups amidst the digitalization of justice, despite facing various challenges such as the digital divide, technological literacy, and resource capacity. Strengthening the capacity of social workers in the field of information technology is needed, as well as adjusting regulations to accommodate their formal role in the digital justice ecosystem.